Schooling: The Way People See It - Parajuli, Mahesh Nath (Journal of Education and Research, 2008)
In this paper, I discuss how people perceive and give meaning to schooling or education. Based largely on field-data, I organize this discussion on four key themes social status and employment, everyday skills and knowledge, gender and caste, and social relationships. While making these discussions I argue that powerful contradicting forces are operating in educational arena, one, local pressures from below for educational opportunities and improvement and the other, from above, resistance to maintain hierarchy. I show how powerful forces at the local level deny access to schooling to women, low castes and the poor. It is true that the access to schooling to these deprived groups has been improved recently. Nevertheless, the discriminatory forces are still powerful illustrating the tension between the agency of these actors and societal structures. DOI: http://dx.doi.org/10.3126/jer.v1i0.7949 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 31-40